Studies of Cryphonectria parasitica (MURR.) BARR subpopulations on Quercus petraea in Ukraine - Radócz, László; Tarcali, Gábor; Irinyi, László; Görcsös, Gábor (Acta Agraria Debreceniensis, 2011)
Chryphonectria parasitica (Murr.) Barr, the casual agent of chestnut blight disease, which is one of the most important fungal pathogens of chestnut (Castanea sativa). The disease seriously affected the chestnut in Northern-America and in Europe as well. It is important to mention that the pathogen does not only infect the chestnut but oak species (Quercus spp.) also. In the Carpathian-Basin, the chestnut is endemic in the Mecsek mountains, in Zala, in Somogy counties but it also can be found in the Danube-Bend. In the Carpathian-Basin (outside Hungary) the chestnut is found in Slovakia, Ukraine, Romania. In our study bark samples infected by Cryphonectria parasitica were collected from Bobovyshche, Serednje and Rostovjatica (Ukraine). The rate of infected chestnut tree were higher than 90% around Bobovyshche and beside chestnut, the symptoms were detected on oak trees as well. We collected bark samples from chestnut and oak as well and then we isolated the pathogen Cryphonectria parasitica in the lab of University of Debrecen. Symptomatological observations, laboratory examinations on fungus morphology, as well as comparisons of ITS sequency homology were made and approved that the causal agent of new disease was Cryphonectria parasitica. Our results proved that the Cryphonectria. parasitica infects oak trees beside chestnut in the Carpathian-Basin. Further studies are needed to determine the VCG (Vegatative Compatibility Group) group of the Cryphonectria parasitica found on oak trees.